Acceptability of the COVID-19 Vaccine among Adults in Saudi Arabia: A Cross-Sectional Study of the General Population in the Southern Region of Saudi Arabia - Yahya S. Alqahtani (Vaccines, 2021)
Vaccines afford protection against infectious diseases. However, a sizeable part of the population refuse vaccinations and continue to dispute the evidence supporting vaccinations. The objective of this study was to determine the prevalence of COVID-19 vaccination uptake and its determinants among the Saudi population in the southern region of Saudi Arabia. A cross-sectional survey studied COVID-19 vaccine acceptance in adults in Saudi Arabia, targeting the general population in the southwestern region. Data were collected through an online survey questionnaire tool. All data were analysed using SPSS version 23.0. The majority (57.29%) of the participants were willing to receive the new COVID-19 vaccine, whereas almost 64% believed it is necessary to take the COVID-19 vaccine to protect oneself and that the vaccine is safe, efficient and effective. The data showed that perceived risk of COVID-19 (p = 0.015), history of previous vaccination against seasonal influenza (p = 0.000), and trust in the healthcare system (p = 0.025) were significant predictors for COVID-19 vaccine acceptance. We conclude that participants’ trust in the healthcare system, perceived risk of contracting COVID-19, and history of previous vaccination against seasonal influenza were significant predictors for COVID-19 vaccine acceptance. Knowing the acceptance rates for the COVID-19 vaccination can aid state agencies, medical practitioners, and other entities in reducing the impact of vaccine avoidance.